1998
DOI: 10.1161/01.cir.98.10.953
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Atrioventricular Junction Ablation and VVIR Pacemaker Versus Pharmacological Treatment in Patients With Heart Failure and Chronic Atrial Fibrillation

Abstract: In patients with heart failure and chronic AF, Abl+Pm treatment is effective and superior to drug therapy in controlling symptoms, although its efficacy appears to be less than that observed in uncontrolled studies because some improvement can also be expected in medically treated patients. Cardiac performance is not modified by the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
167
1
10

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(182 citation statements)
references
References 33 publications
4
167
1
10
Order By: Relevance
“…25 Randomized prospective studies comparing the ''ablate and pace'' modality and pharmacological management in patients with LV dysfunction are rare, and patients of these studies included not only some pure TIC but also many structural heart diseases. 26,27 Present study included only pure TIC patients. We found that control of heart rate was comparable to restoration of sinus rhythm for symptoms and echocardiographic parameters.…”
Section: Treatment Methods and Clinical Outcomesmentioning
confidence: 99%
“…25 Randomized prospective studies comparing the ''ablate and pace'' modality and pharmacological management in patients with LV dysfunction are rare, and patients of these studies included not only some pure TIC but also many structural heart diseases. 26,27 Present study included only pure TIC patients. We found that control of heart rate was comparable to restoration of sinus rhythm for symptoms and echocardiographic parameters.…”
Section: Treatment Methods and Clinical Outcomesmentioning
confidence: 99%
“…Аблация атриовентрикулярного узла в сочетании с имплантацией водителя ритма является высоко эф-фективным методом контроля ЧСС и вызывает умень-шение симптомов [140][141][142][143]. Наибольшего эффекта удается добиться при наличии симптомов или кар-диомиопатии, связанных с тахикардией, которую не уда-ется контролировать с помощью антиаритмических или хронотропных препаратов.…”
Section: с аблация атриовентрикулярного узлаunclassified
“…79 In a randomized controlled study of 66 persons with CHF and chronic AF, AV junction ablation with implantation of a VVIR pacemaker was superior to drug treatment in controlling symptoms. 80 Long-term survival is similar for patients with AF whether they receive radiofrequency ablation of the AV node and implantation of a permanent pacemaker or drug therapy. 81 In 44 patients, mean age 78±5 years, radiofrequency catheter ablation followed by pacemaker implantation was successful in ablating the AV junction in 43 of 44 patients (98%) with AF and a rapid ventricular rate not controlled by drug therapy.…”
Section: Journal Of Atrial Fibrillationmentioning
confidence: 99%